Agents of Economic Development an essential Guide for navigating good, bad, & uncertain - Wade, Neal. (‎Independently published, 2020)
In turbulent and stable times, a good map, and experienced guide can help sort through the twists and turns that are inherent in today?s complex economic development. Throughout this book there are lessons for everyone involved in growing urban, rural, and regional economies ? the volunteer leaders, elected officials and, of course, the men and women who go to work every day creating and sustaining jobs in their communities. Neal and Bill weave each author?s 30+ years? experience at the local, state, private, and academic levels to create an essential guide for economic vitality in these turbulent and changing times. This book can help everyone engaged in community and economic development operate at the highest level of personal and professional excellence.
179p.
Keywords: Sustainable Development